SAPROBIC FUNGI AS BIOCONTROL AGENTS OF HALO BLIGHT (Pseudomonas syringae pv. garcae) IN COFFEE CLONES - Botrel, Dayana Alvarenga; Laborde, Marie Caroline Ferreira; Medeiros, Flávio Henrique Vasconcelos de; Resende, Mário Lúcio Vilela; Júnio, Pedro Martins Ribeiro; Pascholati, Sérgio Florentino; Gusmão, Luís Fernando Pascholati (Coffee Science - ISSN 1984-3909, 2018)
Halo blight caused by Pseudomonas syringae pv. garcae is a limiting disease in coffee production. There are few efficient commercial products on the market to control this disease, and therefore, the prospection of different biocontrol agents is a promising alternative. The objectives in this study were (i) to select saprobic fungi with the potential to control halo blight in coffee clones, and (ii) to evaluate the contributions of induced resistance as control mechanisms. Plants were sprayed with Gonytrichum chlamydosporium, Phialomyces macrosporus, and Moorella speciosa 7 d before inoculation with Pseudomonas. syringae pv. garcae. The area under the halo blight progress curve (AUDPC) and plant growth parameters were evaluated. M. speciose and G. clamydosporium did not reduce the AUDPC and even reduced plant growth in none of the trails compared to the water control. P. macrosporus consistently reduced AUDPC by 42 - 72% and increased plant height by 40%. Thereafter, the contributions of induced resistance was evaluated for the P. macrosporus, selected as the most promising biocontrol agent.. In order to determine induced resistance, phenylalanine ammonia lyase (PAL), peroxidase (POX), and ascorbate peroxidase (APX) activity of plant leaves were measured at two time points after stress challenge. Enzyme activity evaluation demonstrated high activity of POX and PAL at seven days after treatment with the saprobe, and high APX activity after 14 days. The results of this study indicate that P. macrosporus has the potential to be used in the management of coffee halo blight in seedling production, and one mechanism likely involved is induced resistance.